STRATEGI KENDALI ORGANISASI KOMPAS TV DALAM MENINGKATKAN KUALITAS KINERJA TEAM PRODUKSI - Raden Cahyo Prabowo (Communicology: Jurnal Ilmu Komunikasi, 2019)
Abstract Research on Kompas TV's Organizational Control Strategy in Improving Production Team Performance (Case Study Team of the "ROSI" Talkshow Event Program) at Kompas TV in improving the performance of the production team has a purpose to find out how the Kompas TV Organization Control Strategy Improves Production Team Performance (Case Study "ROSI" Talk Show Program Performance Team) at Kompas TV. The theories used in this study include Philip Tompkins's Organizational Control Theory and colleagues. The research paradigm used is Post-positivism. The research approach is qualitative using the Case Study research method. The results of this study are the Compass TV Organizational Control Strategy in Improving Production Team Performance (Case Study Team for a good and quality "ROSI" Talkshow Program) by means of two-way communication between Ms. Rosi Silalahi and the Kompas TV performance team and joint dialogue so that shows talkshow Rosi Kompas TV Becomes quality. In the Rosi Kompas TV talkshow program, the production performance team conducted a dialogue with Rosi on what themes or issues to be raised during the Rosi talk show on the D-Day or Thursday. Keywords: Strategy, Organizational Control, TV Compass, Quality, Performance, Case Study